Strategi Guru dalam Pembelajaran PAI bagi Anak Berkebutuhan Khusus di SMPLB-YPPC Labui - Wahyuni, Fitri (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Learning could be effective and efficient, if the teacher has appropriately learning strategy as well the ability of the students, especially for disable students. So then the teacher’s strategy as teaching PAI is very important. The problem of this research is focused on how the teachers strategy on teaching PAI for disable students of SMPLB-YPPC Banda Aceh.Moreover, the objective of this research is to figure out the strategy of the teacher on teaching PAI for disable students of SMPLB-YPPC Banda Aceh. Research design used in this research is descriptive qualitative method. Then, the location of this research is SMPLB-YPPC Banda Aceh. Subjects of this research are a headmaster and 2 PAI teachers. Method of data collection that used in this research is observation, interview and documentary. The instrument used here is a list of interviews and observations. The technique of data analysis is data reduction, data display, and data verification. The result displays 1) strategy of the teacher on teaching PAI in SMPLB-YPPC Banda Aceh: a) individual groups, b) cooperative, c) behavior modification. 2) Supporting and inhabiting factors on teaching PAI in SMPLB-YPPC Banda Aceh: a) inhabiting factors are students’ parents have less concern, disability of disable students and learning media. 3) Implementation on teaching PAI strategy in SMPLB-YPPC Banda Aceh: a) lesson plan, b) learning implementation, c) evaluation.